Effects of sleep on substance use in adolescents: a longitudinal perspective. (26th May 2017) - Nguyen‐Louie, Tam T.; Brumback, Ty; Worley, Matthew J.; Colrain, Ian M.; Matt, Georg E.; Squeglia, Lindsay M.; Tapert, Susan F.
Abstract: Substance use (SU) and sleep problems appear interrelated, but few studies have examined the influence of adolescent sleep patterns on development of SU disorders. This study prospectively examined the influence of sleep habits on subsequent SU in youth who later transitioned into heavy drinking. At time 1 (T1), participants ( n = 95) were substance‐naive 12‐ to 14‐year‐olds. Path‐analytic models examined whether the effects of T1 risk factors (familial SU disorder, inhibition control, and externalizing and internalizing traits) on time 3 ( M = 19.8 years old) tobacco, alcohol, and cannabis were mediated by time 2 ( M = 15.1 years old) sleep chronotype, daytime sleepiness, and erratic sleep/wake behaviors. Significant direct path effects of T1 risk factors and time 2 sleep behaviors on time 3 SU were found, P s < 0.05. In models that examined the effect of each individual sleep behavior separately on SU, more erratic sleep/wake and greater daytime sleepiness predicted higher lifetime use events for all substances ( P s < 0.01). Higher evening chronotype tendencies predicted lower tobacco and higher alcohol and cannabis lifetime use events ( P s < 0.01). Erratic sleep/wake behaviors mediated the effect of inhibitory control on subsequent SU; less erratic sleep/wake behaviors predicted better inhibition control ( β ̂ = −0.20, P < 0.05). Early‐mid adolescent psychiatric health and sleep behaviors prior to drinking onset predicted greater SU 5 years later. Participants were substance‐naïve at baseline, allowing for the examination of temporal order in the relationship between sleep problems and alcohol use. Early adolescent sleep problems may be an important risk factor for SU in later life. Abstract : Early–mid adolescent psychiatric health and sleep behaviors prior to drinking onset predicted greater alcohol, marijuana, and tobacco use 5 years later. Erratic sleep/wake behavior was a significant mediator in the effect of baseline inhibition control on lifetime substance use events at follow‐up. Participants were substance‐naïve at baseline, allowing for the examination of temporal order in the relationship between sleep problems and alcohol use.